A Combination Prosthesis Using Thimble Copings for Reconstruction of Mutilated Dentition: A Case Report at Nobel Medical College, Biratnagar - Warainch, Robin Singh; Dali, M; Naulakha, D (Birat Journal of Health Sciences, 2017)
Planning and executing the restorative rehabilitation of a severely mutilated dentition is one of the most challenging tasks for the restorative dentist. This case report illustrates an interdisciplinary approach in the treatment of a multifaceted case of partial loss of teeth. A series of provisional prosthesis were used before the final treatment due to extreme complexity of the patient situation. The final treatment was composed of innovatively designed thimble copings, telescopic retainer and cast metal frame work for the rehabilitation of the maxillary and mandibular arch.Birat Journal of Health Sciences Vol.2/No.1/Issue 2/ Jan - April 2017, page: 222-226